2006
DOI: 10.1002/jcb.20747
|View full text |Cite
|
Sign up to set email alerts
|

Modeled gravitational unloading triggers differentiation and apoptosis in preosteoclastic cells

Abstract: Gravity acts permanently on organisms as either static or dynamic stimulation. Understanding the influence of gravitational and mechanical stimuli on biological systems is an intriguing scientific problem. More than two decades of life science studies in low g, either real or modeled by clinostats, as well as experimentation with devices simulating different types of controlled mechanical stimuli, have shown that important biological functions are altered at the single cell level. Here, we show that the human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 70 publications
4
30
0
Order By: Relevance
“…No significant differences were found between untreated and laser-treated 1 × g controls (a, b, c, f, i, j). The samples exposed to modelled microgravity and then to the laser treatment showed a cytoskeletal structure restored and similar to the 1 × g controls (d, h, l) increase in apoptosis, which often occurs in cell cultures exposed to weightless conditions (Uva et al 2002;Monici et al 2006), a microgravity-induced decrease in myoblast proliferation, which has been recently found by other authors (Pache et al 2010), altered protein synthesis/degradation (Moriggi et al 2010), or a combination of these effects.…”
Section: Discussionsupporting
confidence: 69%
“…No significant differences were found between untreated and laser-treated 1 × g controls (a, b, c, f, i, j). The samples exposed to modelled microgravity and then to the laser treatment showed a cytoskeletal structure restored and similar to the 1 × g controls (d, h, l) increase in apoptosis, which often occurs in cell cultures exposed to weightless conditions (Uva et al 2002;Monici et al 2006), a microgravity-induced decrease in myoblast proliferation, which has been recently found by other authors (Pache et al 2010), altered protein synthesis/degradation (Moriggi et al 2010), or a combination of these effects.…”
Section: Discussionsupporting
confidence: 69%
“…Yang et al found the apoptosis in luteal cells induced by clinostat rotation was related to the mitochondrial dysfunction (Yang et al, 2002). Simulated microgravity-induced apoptosis was related to both extrinsic and intrinsic pathways by the evidences of activation of caspase-3 and increases of Fas and Bax in normal thyroid cells and papillary thyroid carcinoma cells (Kossmehl et al, 2003), as well as human endothelial cells (Infanger et al, 2006a) and preosteoclastic FLG 29.1 cells (Monici et al, 2006). Simulated microgravity activates caspase-8 and -3 and the transcription factor NF-jB necessary to stimulate the apoptotic pathway in mice testis (Sharma et al, 2008).…”
Section: Controlmentioning
confidence: 97%
“…The data represent the mean ± SD from three independent experiments (*P < 0.05). (Monici et al, 2006). Yang et al found the apoptosis in luteal cells induced by clinostat rotation was related to the mitochondrial dysfunction (Yang et al, 2002).…”
Section: Controlmentioning
confidence: 98%
“…The simulated weightlessness was produced by averaging the gravity vector via the independent rotation of the two frames. 14 For culturing RAW264.7 cells in the RPM, cultures were seeded in 25 mL culture°a sks and cultured overnight. Then the°asks were completely¯lled with medium to eliminate air bubbles, and diminish turbulence and shear forces.…”
Section: Random Positioning Machine (Rpm )mentioning
confidence: 99%